FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI INFORMASI PELAPORAN KEUANGAN PEMERINTAH DAERAH DENGAN SISTEM PENGENDALIAN INTERN SEBAGAI VARIABEL MODERATING - Saputri, Eliza; Basri, Yesi Mutia; Nur Azlina, Nur Azlina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to analysis the factors that affect the value of financial reporting information local government with internal control system as a moderating variable. The study was conducted on 29 OPD located in Kampar regency in 2017. The sample used as the respondents was taken by using purposive sampling method. The Questionnaires distributed to 87 respondents, and successfully collected again with complete answers obtained from 75 respondents. The analysis tool used in this research is moderated regression analysis (MRA). The results of the tests show that the quality of human resources, utilization of information technology, and organizational commitment affect on the value of local government financial reporting information directly. While the supervision of regional finance does not affect on value of local government financial reporting information. The internal control system does not moderate affect of the Quality of Human Resources, Utilization of Information Technology, Local Financial Supervision, Organizational Commitment in the field of accounting to the Value of Local Government Financial Reporting Information.Keywords : Quality of Human Resources, Utilization of Information Technology, Local Financial Supervision, Organizational Commitment, Internal Control System, Value of Local Government Financial Reporting Information.